2022
DOI: 10.1002/adfm.202203677
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Coordination Microenvironment of Cu(I) in Metal–Organic Frameworks for Enhancing Electroreduction of CO2to CH4

Abstract: The coordination microenvironment of metal active sites in metal–organic frameworks (MOFs) plays a crucial role in its performance for electrochemical CO2 reduction reaction (CO2RR). However, it remains a challenge to clarify the structure–performance relationship for CO2RR catalyzed by MOFs. Herein, a series of MOFs with different coordination microenvironments of Cu(I) sites (CuCl, CuBr, and CuI) to evaluate their performances for CO2RR is synthesized. With the increasing radius of halogen atom, the CO2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 70 publications
2
36
0
Order By: Relevance
“…Therefore, the CO species can bind tightly on the CuO 5 site to form a more stable *CO intermediate (binding energy of −73.4 kJ mol –1 for the CuO 5 site versus that of −48.6 kJ mol –1 for the CuO 4 site in Cu-DBC ) (Figure a), as being verified by PDFT calculations, which promotes further hydrogenation of *CO to yield CH 4 . Similarly, Sun et al designed a series of MOFs with Cu 4 X (X = Cl, Br, or I) clusters (denoted as Cu–Cl , Cu–Br , and Cu–I , respectively) (Figure b) and elaborated the effect of halogen ligand on the electron structure of Cu site for ECR . According to the DFT results, with the increasing radius of the halogen atom from Cl to I, the d- band center of the Cu site positively shifts to the Fermi level, and the formation energies of the key intermediates *CH 2 O and *CH 3 O were successively reduced, leading to an enhanced Faradaic efficiency of CH 4 .…”
Section: Selectivity Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the CO species can bind tightly on the CuO 5 site to form a more stable *CO intermediate (binding energy of −73.4 kJ mol –1 for the CuO 5 site versus that of −48.6 kJ mol –1 for the CuO 4 site in Cu-DBC ) (Figure a), as being verified by PDFT calculations, which promotes further hydrogenation of *CO to yield CH 4 . Similarly, Sun et al designed a series of MOFs with Cu 4 X (X = Cl, Br, or I) clusters (denoted as Cu–Cl , Cu–Br , and Cu–I , respectively) (Figure b) and elaborated the effect of halogen ligand on the electron structure of Cu site for ECR . According to the DFT results, with the increasing radius of the halogen atom from Cl to I, the d- band center of the Cu site positively shifts to the Fermi level, and the formation energies of the key intermediates *CH 2 O and *CH 3 O were successively reduced, leading to an enhanced Faradaic efficiency of CH 4 .…”
Section: Selectivity Controlmentioning
confidence: 99%
“…(a) Optimization of coordination geometry, (b) Decreasing the electronegativity of a coordinated atom, (c) enhancement of cuprophilic interaction, and (d) intensification of an electron-donating effect. Adapted with permission from refs , , and . Copyright 2021 and 2022 American Chemical Society, and from ref .…”
Section: Selectivity Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that the CO 2 -to-CH 4 conversion undergoes multiple proton-coupled electron transfer steps, 28 while the *H adsorption sites for CO 2 protonation are still not clear. We first conducted hydrogen evolution reaction (HER) measurements to investigate water electrolysis for nitrogen-doped (N−C) and undoped carbon (C) materials.…”
mentioning
confidence: 99%